Let’s Stop Corruption in the Judiciary! Judicial Human Resource Architecture as an Integrity-by-Design Framework through a Socio-Legal Approach - Anang Riyan Ramadianto; Suhadi; Indah Sri Utari (RADJA PUBLIKA, 2025)
Corruption within the judiciary poses a systemic threat to the rule of law, undermining legal certainty, institutional credibility, and public trust. Although anti-corruption strategies have traditionally relied on criminal enforcement and external supervision, persistent cases involving judges indicate structural vulnerabilities that remain insufficiently addressed. This article examines judicial human resource architecture as an integrity-by-design framework for preventing corruption within the judicial environment. The study aims to analyze how recruitment systems, promotion and mutation mechanisms, performance evaluation, career development, intrinsic motivation, and organizational fairness influence judges’ integrity as a structural preventive safeguard. Employing a mixed-method socio-legal approach, the research combines normative legal analysis with empirical data collected from 80 judges through a Likert-scale questionnaire. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the validity of constructs and examine causal relationships among variables. The findings demonstrate that merit-based recruitment, transparent promotion systems, and fair performance evaluation significantly strengthen judges’ integrity, while organizational fairness and intrinsic motivation function as reinforcing factors in reducing corruption risks. The study concludes that corruption prevention in the judiciary requires a paradigm shift from reactive enforcement toward institutional design grounded in human resource governance. It recommends the systematic integration of integrity principles into judicial recruitment, evaluation, and career management policies to ensure sustainable anti-corruption outcomes and strengthen the legitimacy of judicial institutions.